Impact of FASN-enriched EVs on endothelial cell function in obstructive sleep apnea hypopnea syndrome - Yuan Tian; Dan Zhang; Huaian Yang; Xiaoli Zhang; Shengqun Xu (Journal of Pharmaceutical Analysis)
Endothelial dysfunction is a key factor linking obstructive sleep apnea hypopnea syndrome (OSAHS) with cardiovascular diseases. In this study, we used advanced proteomics and metabolomics approaches to investigate the impact of extracellular vesicles (EVs) derived from the serum of OSAHS patients on endothelial function. Our multi-omics analysis identified dysregulated pathways related to fatty acid metabolism, apoptosis regulation, and inflammatory responses, highlighting fatty acid synthase (FASN) as a crucial player in OSAHS-induced endothelial dysfunction. Both in vitro and in vivo experiments demonstrated that FASN-enriched EVs impair endothelial cell viability and disrupt metabolic homeostasis, offering new insights for the development of targeted therapies for cardiovascular complications associated with OSAHS.